The Views of Primary Education Teachers of The Municipality of Prizren and Pristina Regarding the Adaptation of The Didactic Environment for Children with Special Needs - Shemsi Morina, Lon Laska (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The inclusiveness of children with special needs in regular schools made necessary studies that focus not only on the changes in approach and variety in teaching, but also on the creation of environments, tools and appropriate materials that approximate the differences of children in the process of learning, including children with special needs. The study in question aimed to shed light on the state of didactic environments in primary education, with a special focus on its adaptation to children with special needs. The problem has been addressed in the theoretical but also in the empirical aspect. Through the theoretical analysis, namely the use of the most contemporary literature, instructions have been given for the adaptation of didactic environments, tools and materials with a special focus on children with special needs. While through semi-structured interviews, we have reflected how the situation is in reality of the adaptation of didactic environments, tools and materials, with a special focus on children with special needs. After the analysis of the results, as well as the findings of the study, based on the defined variables, we gave the necessary recommendations to the relevant institutions in order to change the situation in terms of the adaptation of didactic environments, tools and teaching materials with a special focus on children with special needs.